Compression performances and failure maps of sandwich cylinders with pyramidal truss cores obtained through geometric mapping and snap-fit method. (15th October 2019) - Wang, Jiangtao; Liu, Wenfeng; Kang, Shuai; Ma, Te; Wang, Zhe; Yuan, Wu; Song, Hongwei; Huang, Chenguang
Abstract: The compressive behaviors and failure maps of lightweight all-metallic sandwich cylinders with pyramidal truss cores are studied experimentally and theoretically. Orthotropic truss cores are fabricated through geometric mapping and snap-fit method. Curved facesheets are bonded to the truss cores by two-times vacuum brazing approach to eliminate unbound nodes. The full-field deformation and strain of the sandwich cylinder are measured by using the 3D digital image correlation system. The local buckling of the facesheet, the mode of which is influenced by the truss cores, is observed during the experiment. Theoretical models are developed considering five possible failure modes of the sandwich cylinder under compression, namely, Euler buckling, global buckling of the cylinder, local buckling of facesheet, face yielding and core member buckling. Failure maps are constructed on the basis of the models. The typical failure modes obtained from numerical simulation are consistent with the theoretical prediction.